Methods and Approaches of Decision Support System for Coconut Agroindustry Development and Down-streaming: A Systematic Literature Review and Future Agenda - Wardah, Siti; Wardah, Siti; Marimin, Marimin; Yani, Mohamad; Djatna, Taufik (International Journal of Supply Chain Management, 2020)
Decision support system in development and Down-streaming of coconut-based agroindustry constitutes a meaningful approach for stakeholders in decision making process, in which it is semi-structural process in coconut agroindustry. This current work aimed to identify and analyze a method and approach in development of coconut agroindustry and its downstream, as well as to collaborate and criticize both stages. This work has reviewed 146 scientific articles from 5 main publication databases worldwide published between 2000 – 2018. The identification and classification techniques of this work included multicriteria decision making, financial feasibility study, qualitative and quantitative study, while the methods were generally grouped into decision support system, multicriteria decision making, multi objective decision making, smart system. Currently, methods in decision making system in the area of coconut agroindustry in both downstream and development stage mostly discussed in traditional perspective, without considering spatial intelligent decision support system which enables us to create decision faster. This work successfully built research framework as feed for further model development using smart decision making system covering development and downstream coconut agroindustry with integration of potential area mapping model, product development, and institutional aspect.